Implementasi Ajaran Trilogi Kepemimpinan melalui Pembelajaran Pendidikan Kewarganegaraan di SD Negeri 01 Tawangmangu Karanganyar - Nadziroh; Wachid Pratomo; Chairiyah (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2020)
The results showed that (1) the implementation of the Leadership Trilogyteachings was applied by giving examples, awards, and peer tutors in learning, instilling cooperative attitude, giving moral encouragement or direction to students by teaching rights and obligations as citizens and setting examples or giving good examples, and give a model of an example as a good citizen and always motivate students to be good citizens. (2) Values implemented in Civics Learning are independent values, discipline, self-confidence, mutual respect, respect for opinions, tolerance, character, and courtesy. The value of honesty, responsibility, vision of leadership, and example is implanted in students.(3)The obstacles to the implementation of the trilogy of leadership are students' different abilities in understanding the material taught by the teacher, memorizing the material, and difficult in distinguishing activities carried out in accordance with learning values. Students only act and behave naturally, but have not been able to distinguish the values of these actions. Students do not understand the values in learning and the difficult in applying these values in learning activities in the classroom or in everyday life.